Ethanol Fermentation on Mixed Sugars Using Mixed Culture of Two Yeast Strains - J. Jasman; Irfan Dwidya Prijambada; Chusnul Hidayat; Donny Widianto (Universitas Gadjah Mada, 2013)
The objective of this study was to evaluate the use of mixed cultures of the recommended yeast strainsfrom a previous study on ethanol fermentation using a substrate mixture consisting of sucrose, glucose, andfructose. There were three mixed (combination) cultures namely OUT7096/OUT7913, OUT7096/OUT7921,and OUT7913/OUT7921. The fermentation medium contained sugar mixture consisting of glucose, fructose,and sucrose with a composition generally close to the composition of sugars in sweet sorghum juice. Overall,fermentation is carried out in two stages. First fermentation was performed using the three mixed culturesto determine the best combination based on the concentration of ethanol produced and the concentration ofresidual sugar. Second fermentation was conducted using the best mixed culture obtained from the fi rst stage.This second stage was intended to describe the pattern of the changes in the concentration of ethanol, sugarsand biomass during the fermentation progresses and to determine some kinetic parameters namely ethanolyield (Yp/s), growth yield (Yx/s) and specifi c growth rate (μ). The results of the fi rst fermentation showed thatthe best mixed culture was OUT7913/OUT7921 and the subsequent fermentation using this culture providethe highest ethanol yield (Yp/s) = 0.47 g.g-1 that was reached at 53rd hour, growth yield (Yx/s) = 0.425 g.g-1, andμ = 0.12 hour-1.Keywords : fermentation, ethanol, mixed culture, mixed sugar